High-transmittance moire-free superfine metal grid structure and preparation method thereof
By adopting irregularly shaped ultra-fine metal mesh structure and narrow line width preparation method on the touch display screen, the problems of molar pattern and low transmittance are solved, and higher visual experience and production efficiency are achieved.
Patent Information
- Application Number
- CN202411195397.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2024-12-13
AI Technical Summary
The existing Mesh Mesh line width of Metal Mesh is wide and has a fixed diamond structure, which makes the touch display prone to molar patterns, increasing production costs and time costs, and at the same time, the transmittance is low, affecting the user's visual experience.
Using a high-transparent, molar-free ultrafine metal grid structure, including irregular-shaped unit metal grids, the line width of the Mesh is 1um to 2um. The randomness of the metal grid is ensured through specific preparation methods such as lithography and etching processes. The shape and narrow line width avoid overlap with the LCD display module and improve transmittance.
It effectively prevents the occurrence of molar patterns, reduces production costs and time costs, and improves the transmittance of touch displays and user visual experience.
Smart Images

Figure CN119127004A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal grid structure, and in particular to a highly transparent ultrafine metal grid structure without moiré patterns and a preparation method thereof. Background Art
[0002] The touch screen consists of a touch screen and a liquid crystal display module, and the Metal Mesh is set on the touch screen. The mesh line width of a conventional Metal Mesh is generally 3um to 5um, and the shape of the Metal Mesh metal grid is fixed to a diamond shape, while the liquid crystal display module has a fixed RGB array, and the relative distance and relative angle of its RGB array units remain unchanged.
[0003] When the metal grid is a diamond structure, since the lengths of the four sides of the diamond structure are fixed, the minimum angle a between the two sides of the diamond, the angle b between the TX and RX Mesh line edges of the metal grid in the same sequence of the same position sequence channel, and the angle c formed by the TX Mesh line and the long side of the liquid crystal display module are all fixed. The metal grid array with an overall diamond structure is easily overlapped with the fixed RGB array of the liquid crystal display module. When the two similar arrays overlap, visible light passes through the metal grid array of the diamond structure and the RGB array of the liquid crystal display in turn. When the human eye observes the touch screen, superimposed stripes of different colors will be visually generated. This stripe is the so-called moiré phenomenon, which greatly affects the user's visual effect. Therefore, when matching different liquid crystal display modules, it is necessary to continuously adjust the angle of the Metal Mesh metal grid to match the RGB array of the liquid crystal display to prevent the touch screen from having moiré phenomena, thereby increasing production costs and time costs.
[0004] Secondly, due to the wide mesh line width, when natural light is incident on the touch screen surface, the wider mesh line width will block part of the natural light, reducing the luminous flux passing through the touch screen, reducing the screen-to-body ratio of the touch display, resulting in a decrease in the transmittance of the touch screen, affecting the user's visual experience. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-transmittance, moiré-free ultrafine metal grid structure and a preparation method thereof, which can effectively prevent the occurrence of moiré on the touch display screen, reduce production costs and time costs, and provide users with a good visual experience.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a highly transparent ultra-fine metal grid structure without moiré, comprising a metal grid pattern arranged on a touch screen, wherein the metal grid pattern is composed of a plurality of connected unit metal grids; each of the unit metal grids is of an irregular shape, and the vertices of each of the unit metal grids are not on a straight line;
[0007] The minimum angle a between the two sides of each unit metal grid is 0° to 180°;
[0008] The angle b between the Mesh line edges of TX and RX of the same sequence unit metal mesh of the same position sequence channel is 0° to 45°, and the angle c formed by the Mesh line of TX and the long side of the liquid crystal display module is 0° to 90°.
[0009] Furthermore, the unit metal grid is an irregular quadrilateral, and the specifications of each unit metal grid are different; wherein, the minimum angle a between the two sides of each unit metal grid is 30°; the angle b between the Mesh line edges of TX and RX of the same sequence unit metal grid of the same position sequence channel is 0°; and the angle c formed by the Mesh line of TX and the long side of the liquid crystal display module is 60°.
[0010] Furthermore, the unit metal grid is an irregular polygon, and the size specifications of each unit metal grid are different; wherein, the minimum angle a between the two sides of each unit metal grid is 120°; the angle b between the TX and RX Mesh line edges of the same sequence unit metal grid of the same position sequence channel is 30°; and the angle c formed by the TX Mesh line and the long side of the liquid crystal display module is 90°.
[0011] Furthermore, the mesh line width of the TX and RX is 1um to 2um.
[0012] A method for preparing a highly transparent ultrafine metal grid structure without moiré patterns comprises the following steps:
[0013] S1. Preparing a copper film having a blackened layer;
[0014] S2. Coating an organic photoresist of a mixture of propylene glycol methyl ether acetate, phenolic resin and photosensitizer on the front side of the copper film with a coating thickness of 1um to 3um, and baking the photoresist at 90°C to 120°C for 5min to 15min; then coating an organic photoresist on the surface of the copper film with a coating thickness of 1um to 3um, and baking the photoresist at 90°C to 120°C for 5min to 15min;
[0015] S3. The coated and cured organic photoresist is exposed to light with an exposure energy of 90mj to 120mj, and the mask circuit used during exposure is the metal grid structure as claimed in claim 1;
[0016] S4. The exposed copper film is developed using a developer, wherein the developer is a colorless and transparent inorganic alkaline solution having a concentration of 0.2% to 0.5%, a development temperature of 25°C to 45°C, a development speed of 1.5m / min to 3.5m / min, and a development time of 1min to 3min;
[0017] S5. The developed copper film is etched using an etching solution consisting of 10% copper sulfate, 8% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and an etching additive, with an etching temperature of 30°C to 50°C, an etching speed of 1m / min to 3m / min, and an etching time of 3min20s to 3min40s;
[0018] S6. Using a stripping solution to strip the etched copper film;
[0019] S7. After the copper film is stripped, it is coated and rolled up to obtain an ultrafine metal grid structure.
[0020] Furthermore, the steps of step S1 are as follows:
[0021] A 50nm-150nm copper oxide or nitrous oxide blackening layer is plated on the front and back sides of 50um or other thickness PET by physical vapor deposition process, and then a 300nm-700nm thick copper film is plated on the surface of the front and back blackening layers, and finally a 50nm-150nm copper oxide or nitrous oxide blackening layer is plated again on the surface of the front and back copper films to obtain a copper film with a blackening layer.
[0022] Furthermore, the stripping solution is a colorless to light yellow transparent and clear mixed solution of organic base and inorganic base, with a concentration of 30g / L to 50g / L, a stripping temperature of 30℃ to 40℃, a stripping speed of 1m / min to 3m / min, and a stripping time of 1min to 3min.
[0023] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0024] The high-transmittance, moiré-free ultrafine metal grid structure and preparation method thereof of the present invention are characterized in that each unit metal grid is a structure with a random shape, and the vertices of each unit metal grid are not on a straight line, so that the touch screen and the display screen will not have moiré phenomenon when they are matched, thereby reducing production cost and time cost.
[0025] Secondly, the mesh line width is between 1um and 2um, so there will be no visual overlap between the metal mesh pattern array and the RGB array of the LCD display, and no moiré phenomenon will occur.
[0026] Moreover, since the width of the metal mesh line is 1um to 2um, the area of metal in the visible area is reduced. When the area of the visible area remains unchanged, the screen-to-body ratio of the touch display will increase. The narrower metal mesh line can improve the screen-to-body ratio and transmittance of the touch screen. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The technical solution of the present invention is further described below in conjunction with the accompanying drawings:
[0028] Figure 1 A schematic diagram of the structure of a metal grid pattern in one embodiment of the present invention;
[0029] Figure 2 is a schematic structural diagram of a metal grid pattern in another embodiment of the present invention;
[0030] Figure 3 A method for preparing a highly transparent ultrafine metal grid structure without moiré in one embodiment of the present invention;
[0031] Among them: 1. Unit metal grid; 2. TX; 3. RX; 4. Long side of the LCD display module. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.
[0033] The present invention provides a highly transparent ultrafine metal mesh structure with no moiré and a preparation method thereof, so as to solve the problems in the prior art that the conventional Metal Mesh has a wide mesh line width and is a fixed diamond metal mesh, which requires repeated moiré matching tests, increases production costs and time costs, and has a low screen-to-body ratio and low transmittance, affecting the user's visual experience.
[0034] For ease of understanding, the specific process in the embodiment of the present application is described below. In the embodiment of the present application, a high-transmittance, moiré-free ultrafine metal grid structure includes a metal grid pattern arranged on a touch screen, wherein the metal grid pattern is composed of a plurality of connected unit metal grids 1, each of which is an irregular shape, and the vertices of each unit metal grid are not on a straight line; the vertices are randomly distributed with an offset distance in the horizontal direction; the minimum angle a of each unit metal grid is 0° to 180°; the angle b of the mesh line edges of TX2 and RX3 of the same sequence unit metal grids of the same position sequence channel is 0° to 45°, and the angle c formed by the mesh line of TX and the long side of the liquid crystal display module is 0° to 90°.
[0035] In the high-transmittance and moiré-free ultrafine metal grid structure of the present invention, each unit metal grid is a structure with a random shape, and the vertices of each unit metal grid are not on a straight line, so that the touch screen and the display screen will not have moiré phenomenon when they are matched.
[0036] based on Figure 1 Furthermore, the unit metal grid 1 in this case is composed of a random quadrilateral, and the size specifications of each random quadrilateral are different. Countless different unit metal grids constitute the metal grid pattern of the touch screen. The length of each side of the random quadrilateral is different, and the minimum angle between two sides is angle a, which is between 5° and 85°. In this embodiment, the minimum angle between the two sides of the first unit metal grid 1 is a. 1 =30°; the angle between the TX and RX mesh lines of the same sequence unit metal mesh of the same position sequence channel is angle b, which is between 0° and 45°. For example, the angle b between the left mesh edge of the first unit metal mesh of the TX1 channel and the left mesh edge of the first unit metal mesh of the RX1 channel is 1 =0°; the angle between the TX Mesh line and the long side 4 of the LCD module is the c angle, which is between 0° and 90°. For example, the angle between the left side of the first unit metal mesh of the TX1 channel and the long side 4 of the LCD module is c. 1 =60°.
[0037] based on Figure 2 Furthermore, the unit metal grid 1 in this case is composed of random quadrilaterals and random hexagons, and countless different unit metal grids form the metal grid pattern of the touch screen. The length of each side of the unit random polygon is different, and the minimum angle between the two sides of the unit metal grid 1 is angle a, which is between 0° and 180°. In this embodiment, the minimum angle between the two sides of the first unit metal grid 1 is a 1=120°; the angle between the TX and RX mesh lines of the same sequence unit metal mesh of the same position sequence channel is angle b, which is between 0° and 45°. For example, the angle b between the left mesh edge of the first unit metal mesh of the TX1 channel and the left mesh edge of the first unit metal mesh of the RX1 channel is 1 =30°; the angle between the TXMesh line and the long side of the LCD module is the c angle, which is between 0° and 90°. For example, the angle between the left side of the mesh of the first unit metal mesh of the TX1 channel and the long side of the LCD module is c. 1 =90°.
[0038] The high-transmittance and moiré-free ultrafine metal grid structure of the present invention has a unit metal grid 1 that is not a diamond structure but a random shape structure, whose shape side lengths are different, and the minimum angle a between the two sides of the unit metal grid 1, the angle b between the TX and RX Mesh line sides of the unit metal grid 1 in the same sequence of the same position sequence channel, and the angle c formed by the TX Mesh line and the long side 4 of the liquid crystal display module are all not fixed. When the array of a certain unit metal grid A overlaps with the fixed RGB array of the liquid crystal display module, since the random shape metal grids are all different, the arrays of other unit metal grids will not overlap with the fixed RGB array of the liquid crystal display module, so that the overall metal grid array is difficult to overlap with the fixed RGB array of the liquid crystal display module, and visible light passes through the metal grid array with random shape and the RGB array of the liquid crystal display screen in turn, and no superimposed stripes are generated when the human eye observes the touch screen, and no moiré phenomenon is generated, thereby improving the user experience and reducing the cost.
[0039] As a further embodiment of the present application, the mesh line width of the unit metal mesh of the present invention is between 1um and 2um. Under the intensity of natural light, the touch screen is rotated at a certain angle and the touch screen is observed closely. The mesh line of the metal mesh cannot be seen, and the ultra-fine metal mesh mesh line is "hidden". When the human eye observes the touch screen, the visible light passes through the metal mesh pattern array and the RGB array of the liquid crystal display in turn. In fact, the visible light observed by the naked eye only passes through the RGB array of the liquid crystal display, and the metal mesh pattern array is visually hidden. Therefore, there will be no visual superposition of the metal mesh pattern array and the RGB array of the liquid crystal display, and no moiré phenomenon will occur.
[0040] At the same time, the screen-to-body ratio of the touch display is the ratio of the area occupied by the non-metallic mesh in the visible area, that is, screen-to-body ratio = (visible area area - metal mesh area in the visible area) / visible area. As the metal mesh line width is reduced from 3um to 5um to 1um to 2um, the area of metal in the visible area is reduced. When the visible area remains unchanged, the screen-to-body ratio of the touch display will increase. At the same time, when visible light passes through the metal mesh, the luminous flux of visible light passing through the metal mesh will increase due to the reduction of the metal mesh line by 1.5 to 5 times, which can improve the transmittance of the touch screen. Therefore, narrower metal mesh lines can improve both the screen-to-body ratio and transmittance of the touch screen.
[0041] In addition, the present invention also discloses a method for preparing a highly transparent ultrafine metal mesh structure without moiré. Specifically, the preparation method prepares an ultrafine circuit with extremely narrow mesh line width and good etching effect through mask compensation design, adjustment of exposure energy and selection of etching solution system and concentration.
[0042] Among them, the orthogonal experimental design for mask design value, mask exposure energy and Mesh line width is shown in the following table.
[0043]
[0044] From this table, it can be seen that the design value of the line on the mask is greatly different from the actual exposure, development, and etching Mesh line width formed. This is because there will be a certain degree of side display phenomenon in the development process, and a certain degree of side erosion phenomenon in the etching process. At the same time, different concentrations of developer and etching solution, side display and side erosion will cause the Mesh line after etching to be smaller than the design value of the mask. Therefore, when designing a Mesh line with a certain line width, it is necessary to increase the compensation design for the line on the mask. The present invention increases the compensation design for the width of the mask line to compensate for the side display and side erosion, and prepares a Mesh line that meets the required line width. From the results of the orthogonal experimental design of the mask design value, the mask exposure energy, and the Mesh line width, to achieve a 1um~2um metal mesh Mesh line, the mask line can be designed to be 4um~4.5um, and the exposure energy is between 90mj~120mj, and a Mesh line with a line width of 1.4um~2.0um can be prepared.
[0045] The orthogonal experimental design for the etching solution system and concentration is shown in the following table.
[0046]
[0047] Etching liquid 1, etching liquid 2, etching liquid 3, and etching liquid 4 are all exposed, developed, and etched under the conditions of a mask line design of 4.0um and an exposure energy of 100mj. Theoretically, yellow edges appear during etching and the etching time needs to be increased; the longer the etching time, the narrower the Mesh line, but the greater the risk of etching breakage.
[0048] Etching solution 1 is composed of 10% copper sulfate, 5% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and other etching additives. Within the etching time of 3min to 3min20s, the Mesh line can meet 1um to 2um, but the line has different degrees of yellow edge phenomenon. After 3min20s, the etching line is broken, and the overall etching effect is not good.
[0049] Etching solution 2 is composed of 5% copper sulfate, 5% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and other etching additives, which reduces the content of copper sulfate. Within the etching time of 3min to 3min20s, the Mesh line can meet 1um~2um, but the line has different degrees of yellow edge phenomenon. After 3min20s, the etching line is broken, and the overall etching effect is not good.
[0050] Etching solution 3 is composed of 15% copper sulfate, 8% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and other etching additives. During the etching time of 3min to 3min40s, the Mesh line can meet 1um to 2um, but the line has different degrees of yellow edge phenomenon. After 3min40s, the etching line is broken, and the overall etching effect is not good.
[0051] Etching liquid 4 is composed of 10% copper sulfate, 8% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and other etching additives. When etching for 3 minutes, the Mesh line can meet the requirement of 1um~2um, but the line has a slight yellow edge phenomenon; when the etching time is extended, the Mesh line can meet the requirement of 1um~2um within the etching time of 3min20s~3min40s, and the line does not have a yellow edge phenomenon; when the etching time is further extended by 4min, the Mesh line has a disconnection phenomenon. Therefore, etching liquid 4 can meet the requirement of 1um~2um of the Mesh line within the etching time of 3min20s~3min40s, and there will be no yellow edge and disconnection phenomenon, and the etching effect is the best.
[0052] The present invention can prepare ultra-fine lines with extremely narrow mesh line width and good etching effect through the above metal mesh optimization design, optimization of mask compensation design, adjustment of exposure energy and selection of etching solution system and concentration, so that the touch screen has no moiré phenomenon and has a high screen-to-body ratio and transmittance. The metal mesh is a random metal mesh design, and is exposed and developed under the conditions of a mask line design of 4.0um to 4.5um and an exposure energy of 90mj to 120mj, and is etched in an etching solution containing 10% copper sulfate for 3min20s to 3min40s, so that a highly transparent ultra-fine metal mesh without moiré can be prepared.
[0053] Specifically, a method for preparing a highly transparent ultrafine metal grid structure without moiré patterns has the following steps:
[0054] S1. Obtaining a copper film having a blackened layer;
[0055] Specifically, a 50nm-150nm copper oxide or nitride blackening layer is plated on the front and back sides of 50um or other thickness PET by physical vapor deposition process, and then a 300nm-700nm copper film is plated on the surface of the front and back blackening layers, and finally a 50nm-150nm copper oxide or nitride blackening layer is plated again on the surface of the front and back copper films to obtain a copper film with a blackening layer;
[0056] S2. Using precision coating technology, an organic photoresist whose main components are a mixture of propylene glycol methyl ether acetate, phenolic resin, and photosensitizer is coated on the front of the copper film with a coating thickness of 1um to 3um, and the photoresist is baked at 90°C to 120°C for 5min to 15min; then, the organic photoresist is coated on the surface of the copper film with a coating thickness of 1um to 3um, and the photoresist is baked at 90°C to 120°C for 5min to 15min;
[0057] S3. The organic photoresist coated and cured is exposed using a contact exposure machine, the exposure energy is 100mj, and the mask circuit used during exposure is the unit metal grid structure of the present invention;
[0058] S4. The exposed copper film is developed using a developer, wherein the developer is a colorless and transparent inorganic alkaline solution having a concentration of 0.2% to 0.5%, a development temperature of 25°C to 45°C, a development speed of 1.5m / min to 3.5m / min, and a development time of 1min to 3min;
[0059] S5. Etching the developed copper film with an etching solution consisting of 10% copper sulfate, 8% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and other etching additives, at an etching temperature of 30°C to 50°C, an etching speed of 1m / min to 3m / min, and an etching time of 3min40s;
[0060] S6. The etched copper film is stripped using a stripping solution, the stripping solution is a colorless to pale yellow transparent and clear mixed solution of organic alkali and inorganic alkali, the concentration is 30g / L~50g / L, the stripping temperature is 30℃~40℃, the stripping speed is 1m / min~3m / min, and the stripping time is 1min~3min;
[0061] S7. The stripped copper film is coated and rolled up to obtain an ultra-fine metal grid structure with high transparency and no moiré.
[0062] In summary, through the preparation method of the present invention, a highly transparent ultrafine metal grid structure with no moiré can be prepared, so that the touch screen will not produce moiré phenomenon, while improving the screen-to-body ratio and transmittance of the touch display screen, enhancing the user's visual experience.
[0063] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A highly transparent ultrafine metal grid structure without moiré, characterized in that: A metal grid pattern is provided on the touch screen, wherein the metal grid pattern is composed of a plurality of connected unit metal grids; each of the unit metal grids is irregular in shape, and the vertices of each of the unit metal grids are not on a straight line; The minimum angle a between the two sides of each unit metal grid is 0° to 180°; The angle b between the Mesh line edges of TX and RX of the same sequence unit metal mesh of the same position sequence channel is 0° to 45°, and the angle c formed by the Mesh line of TX and the long side of the liquid crystal display module is 0° to 90°.
2. The high-transmittance, moiré-free ultrafine metal grid structure according to claim 1, characterized in that: The unit metal grid is an irregular quadrilateral, and the specifications of each unit metal grid are different; wherein, the minimum angle a between the two sides of each unit metal grid is 30°; the angle b between the Mesh line edges of TX and RX of the same sequence unit metal grid of the same position sequence channel is 0°; and the angle c formed by the Mesh line of TX and the long side of the liquid crystal display module is 60°.
3. The high-transmittance, moiré-free ultrafine metal grid structure according to claim 1, characterized in that: The unit metal grid is an irregular polygon, and the size specifications of each unit metal grid are different; wherein, the minimum angle a between the two sides of each unit metal grid is 120°; the angle b between the TX and RX Mesh line edges of the same sequence unit metal grid of the same position sequence channel is 30°; the angle c formed by the TX Mesh line and the long side of the liquid crystal display module is 90°.
4. The high-transmittance, moiré-free ultrafine metal grid structure according to claim 1, characterized in that: The mesh line width of the TX and RX is 1um to 2um.
5. A method for preparing a highly transparent ultrafine metal grid structure without moiré, characterized in that: The steps include: S1. Preparing a copper film having a blackened layer; S2. Coating an organic photoresist of a mixture of propylene glycol methyl ether acetate, phenolic resin and photosensitizer on the front side of the copper film with a coating thickness of 1um to 3um, and baking the photoresist at 90°C to 120°C for 5min to 15min; then coating an organic photoresist on the surface of the copper film with a coating thickness of 1um to 3um, and baking the photoresist at 90°C to 120°C for 5min to 15min; S3. The coated and cured organic photoresist is exposed to light with an exposure energy of 90mj to 120mj, and the mask circuit used during exposure is the metal grid structure as claimed in claim 1; S4. The exposed copper film is developed using a developer, wherein the developer is a colorless and transparent inorganic alkaline solution having a concentration of 0.2% to 0.5%, a development temperature of 25°C to 45°C, a development speed of 1.5m / min to 3.5m / min, and a development time of 1min to 3min; S5. The developed copper film is etched using an etching solution consisting of 10% copper sulfate, 8% ethylenediaminetetraacetic acid, 1% fluorine surfactant, and an etching additive, with an etching temperature of 30°C to 50°C, an etching speed of 1m / min to 3m / min, and an etching time of 3min20s to 3min40s; S6. Using a stripping solution to strip the etched copper film; S7. After the copper film is stripped, it is coated and rolled up to obtain an ultrafine metal grid structure.
6. The method for preparing a metal mesh structure according to claim 5, characterized in that: The steps of step S1 are as follows: A 50nm-150nm copper oxide or nitrous oxide blackening layer is plated on the front and back sides of 50um or other thickness PET by physical vapor deposition process, and then a 300nm-700nm thick copper film is plated on the surface of the front and back blackening layers, and finally a 50nm-150nm copper oxide or nitrous oxide blackening layer is plated again on the surface of the front and back copper films to obtain a copper film with a blackening layer.
7. The method for preparing a metal mesh structure according to claim 5, characterized in that: The stripping solution is a colorless to light yellow transparent and clear mixed solution of organic alkali and inorganic alkali, with a concentration of 30g / L to 50g / L, a stripping temperature of 30°C to 40°C, a stripping speed of 1m / min to 3m / min, and a stripping time of 1min to 3min.
Citation Information
Cited By
Structure and method for eliminating Moore interference fringes of LED display screen
CN119724050A
Capacitive touch sensor and preparation method thereof
CN122111261A
